Analisis Kepuasan Wisatawan Terhadap Layanan Transportasi Online Untuk Mobilitas Pariwisata Dengan Metode Fuzzy Survqual (Studi Kasus Provinsi Bali) - I Kadek Suyadnya; I Putu Satwika; Bagus Wahyu Putu Nirmala (Primakara University, 2022)
Development of technology and information in the modern era that is now sophisticated, the dissemination and receipt of information is now very easy for everyone to do. Technological advances have also led to trends in the use of information technology in various aspects and the media globally. One aspect of the use of this technology can be used in the field of tourism which is commonly referred to as smart tourism where in general smart tourism aims to develop infrastructure and information and communication capabilities in order to improve management/governance, facilitate service/product innovation, and improve the tourist experience.Bali Province is one of the most prominent provinces in Indonesia in the field of tourism where many tourists vacation in Bali. However, in the field of transportation, Bali does not yet have mass transportation that is connected throughout Bali. Because the problems that are not only in Bali, there is the use of technology with the existence of startups in the field of online transportation. This online transportation provider provides various services such as delivery, purchasing food, paying for tickets and others. The existence of online transportation is an alternative for tourists for their mobility, to evaluate the satisfaction of using this transportation, the Fuzzy Servqual method is used. Fuzzy Servqual measures per dimension attribute of service quality so that the accuracy of the data per dimension can be known.